Mergers & acquisitions integration handbook : helping companies realize the full value of acquisitions - Whitaker, Scott C., 1963- (Wiley finance series, 2012)
Proven strategies and tactics to manage the integration of acquired and/or merged companies Mergers & Acquisitions Integration Handbook is a comprehensive resource to help companies create a scalable post merger or acquisition integration process and framework that accelerates operating and business benefit goal realization. Includes tools, templates, forms, examples and checklists to provide a no nonsense "handbook" style approach to managing an effective integration. Helps integration managers quickly get up to speed on various integration challenges, including guidance on developing detailed.